Covering-Based Rural Road Network Methodology for Hilly Regions of Developing Countries: Application in Nepal - Shrestha, Jagat Kumar (2016)
This work provides a practical approach for the definition of rural road networks in hilly regions of developing countries. The proposed methodology enables the determination of obligatory points for the road network, which provides basic accessibility to settlements within a specified maximum walking time. The proposed methodology, based on a geographic information system (GIS), takes into account the regions’ main characteristics (i.e., trails slope and availability), and does not require significant data. Moreover, simplifications to the method are proposed herein, allowing it to be used even without a GIS; thus making it a more practical, realistic, and userfriendly approach for obtaining real-world road networks of hilly regions in developing countries